The analysis of language attitude of gen-Z students towards EFL in urban and suburban areas - Uswatunnisa, Uswatunnisa; Mursyid, Andi Miftahul Maulidil; Rahmat, Rahmat (Universitas Islam Sultan Agung, 2025)
Analyzing EFL students’ language attitudes is essential, given the uniform national curriculum across Indonesia. The urban-suburban EFL proficiency gap shows greater challenges for suburban teachers. This study explores Gen-Z students' attitudes toward EFL in South and West Sulawesi. A mixed-method (Qual-Quan) design was used, combining classroom observations and interviews to gather concrete data on students’ reactions to English use in the teaching-learning process, conducted over three separate days. The researchers distributed a 14-item language attitude questionnaire covering beliefs, feelings, and tendencies. The research finds that urban Gen-Z students showed generally positive attitudes—enthusiastic, adaptable, and willing to use English even when optional, while still retaining regional accents with pride. In short, They were found to adapt linguistically to their interlocutors, indicating openness and pride in using English despite retaining traces of their regional accent. In contrast, suburban students showed mostly negative attitudes toward English, often mocking peers’ mistakes and feeling shy to speak. Yet, in individual tasks, they were more serious, revealing resistance shaped by peer pressure and strong local language loyalty. The findings underscore the significant role of social context, peer influence, and ethnolinguistic identity in shaping language attitudes among Generation Z in multilingual regions. Nonetheless, the researchers would highly recommend for future scholars to develop specific EFL curriculum for suburban students for better outcomes on English mastery.